Stabilitas vs. Efisiensi : Studi Komparatif Kinerja Keuangan Bank Syariah dan Konvensional di Indonesia (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to comparatively analyze the financial performance of Islamic banks and conventional banks in Indonesia during the post-pandemic period (2021–2023). The research method applied is a comparative quantitative approach by examining five key financial ratios: CAR, NPL/NPF, ROA, ROE, and BOPO, using data from six major banks listed on the Indonesia Stock Exchange. Secondary data from annual financial reports were analyzed through descriptive statistics and an Independent Samples t-test. The results indicate significant differences in financial performance between Islamic and conventional banks across several ratios. In terms of capital adequacy (CAR), Islamic banks recorded an average of 30.15% compared to 24.95% for conventional banks, with t = -2.154 and sig. 0.045, reflecting stronger capitalization. Conversely, conventional banks outperformed in return on equity (ROE), averaging 19.50% compared to 12.85% for Islamic banks, with t = 3.122 and sig. 0.006, suggesting higher shareholder returns. Regarding operational efficiency (BOPO), conventional banks posted a lower average of 68.50% versus 76.90% for Islamic banks, with t = -2.890 and sig. 0.011, indicating better cost efficiency. Meanwhile, NPL/NPF (2.58% vs. 2.45%; sig. 0.442) and ROA (2.95% vs. 2.75%; sig. 0.687) showed no significant differences, implying comparable asset quality and profitability from assets in both groups. In conclusion, a trade-off between stability and efficiency emerges as the key distinguishing characteristic between the two banking systems